2015
DOI: 10.5897/ajb2015.14641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some phytohormones on growth characteristics of Chlorella sorokiniana IAM-C212 under photoautotrophic conditions

Abstract: The effects of some phytohormones [indole acetic acid (IAA), indole butyric acid (IBA), gibelleric acid (GA 3), and kinetin] on cell dry weight, cell number, cell size, protein and chlorophyll contents of Chlorella sorokiniana IAM-C212 were investigated under photoautotrophic conditions. Treatment with IAA (15 mg/l) and IBA (15 mg/l) resulted in significantly higher dry cell weight and cell number than the control (P < 0.05) but there were no significant effects of GA 3 and kinetin on cell growth as expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In the case of hormone supplementation, the present study showed a gradual increase in growth by increasing of IAA up to T5 (which represented 129.0% higher than the control), then showed gradual reduction at higher IAA concentrations. The present results agree with the data obtained by Fabian et al [34] who reported that the treatment of Chlorella sorokiniana with 10 mg L −1 IAA results in the highest dry weight, representing about 9-folds higher than the control. A similar effect was recorded with Parachlorella kessleri, where a positive correlation was recorded with IAA and microalgal growth [35].…”
Section: Effect On Biomass Productionsupporting
confidence: 93%
“…In the case of hormone supplementation, the present study showed a gradual increase in growth by increasing of IAA up to T5 (which represented 129.0% higher than the control), then showed gradual reduction at higher IAA concentrations. The present results agree with the data obtained by Fabian et al [34] who reported that the treatment of Chlorella sorokiniana with 10 mg L −1 IAA results in the highest dry weight, representing about 9-folds higher than the control. A similar effect was recorded with Parachlorella kessleri, where a positive correlation was recorded with IAA and microalgal growth [35].…”
Section: Effect On Biomass Productionsupporting
confidence: 93%
“…SB1 (Figure S1). Studies on the influence of IAA on the biomass growth in Chlorella sorokiniana have already been reported by Ozioko et al in 2015, where a 10 mg/L IAA has resulted in a 9.5-fold increase in the cell concentration.…”
Section: Resultsmentioning
confidence: 90%
“…Corroborating withBryant, Edwards, and Robinson (2016), the use of nitrogen fertilization (50 kg N/ha) combined with sprays of gibberellin increased DM yields. It is worth emphasizing the influence of the hormonal compound used in the formation of structures such as leaf, stem and root, already mentioned in experiment 1(Tables 4 and 5).Chlorophyll content, protein, cell growth and biomass production were more pronounced in plants under the synergistic effect of the addition of auxins and gibberellins, suggesting an increase in the cellular concentrations of these compounds(Ozioko, Chiejina, & Ogbonna, 2015). The increase in the contents of chlorophyll a with the use of growth regulator, combined with the result of mass yield, justifies the efficiency of use of exogenous compounds in the regulation of plant development as they exert functions in the signaling network of photosynthetic processes.…”
mentioning
confidence: 72%